Factors affecting preschool teachers' implementation of STEAM activities: A quantitative study in Vietnam - Manh-Tuan Nguyen; Tú Anh Hà; Huyen-Anh Mai; Kieu-Trang Thi Vu; Minh Quang Nguyễn (Social Sciences and Humanities Open)
A number of studies have shown that STEAM education should begin in early childhood when children are naturally inclined to question, create, investigate and explore. The quality of STEAM education in preschools significantly depends on teachers as they are in charge of organizing STEAM activities for their students. In order to enhance teachers' practice, this study aims to explore the factors impacting preschool teachers' implementation of STEAM activities in the context of Vietnam. The study collected data from 416 preschool teachers currently working in Hanoi City, Vinh Phuc and Dien Bien province. Both the measurement and structural models were examined by applying the Covariance based-Structural Equation Modeling (CB-SEM) through the application of IBM SPSS Statistics 25. The results show that the most influential factor was support from school managers, followed by specialized knowledge of the STEAM fields, and professional attitudes toward STEAM education. On the contrary, in Vietnamese early childhood education, materials and facilities and support from other forces such as parents, colleagues and experts did not significantly influence teachers' practice. The study contributes to the building of scales measuring teachers' professional attitudes toward STEAM education and teachers’ practice of organizing STEAM activities. From the results of this research, policy recommendations have been proposed to improve the quality of STEAM education in the Vietnamese context.